Environment-friendly nano modified polyaniline composite material for electric grounding body and preparation process of environment-friendly nano modified polyaniline composite material

Through the combination of nano-modified polyaniline materials with low-density polyethylene, styrene-butadiene thermoplastic elastomers and additives, the dispersion and mechanical properties of polyaniline are improved by using elocide and enhanced fillers, and the conductive polymers are solved in practice. The stability and processability issues in the application have achieved efficient improvement in conductivity.

CN119286099AActive Publication Date: 2025-01-10ZHANGYE POWER SUPPLY COMPANY OF STATE GRID GANSU ELECTRIC POWER +1
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
CN202411601356.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-10
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

In practical applications, conductive polymers are limited by the problems of expensive, poor processability and poor stability. In particular, polyaniline materials are difficult to dissolve and easily agglomerate, which is not conducive to the optimization of the conductive properties and mechanical properties of conductive composite polymers.

Method used

The combination of nano-modified polyaniline materials and low-density polyethylene, styrene-butadiene thermoplastic elastomers and additives is used to nanomodify polyaniline through elosite to prepare polyaniline as the core and polyaniline as the The core-shell structure nanocomposite material of the shell is added, and reinforced fillers and modified fibers are added during the preparation process to improve the dispersion and mechanical properties of the material.

Benefits of technology

The mechanical properties and electrical conductivity of conductive composite polymers are improved, making them suitable for a variety of environments, enhancing the toughness and electrical conductivity of the material, and solving the dispersion and stability of polyaniline in matrix materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an environment-friendly nano-modified polyaniline composite material for an electric grounding body and a preparation process of the environment-friendly nano-modified polyaniline composite material, and relates to the field of conductive polymer materials, the environment-friendly nano-modified polyaniline composite material comprises a nano-modified polyaniline material, low-density polyethylene, a styrene-butadiene thermoplastic elastomer and an additive, the weight part ratio of the nano-modified polyaniline material to the low-density polyethylene to the styrene-butadiene thermoplastic elastomer to the additive is (4-5): (10-11): (3-4): (1-2), in the preparation process of the conductive composite polymer, the reinforcing filler and the modified fibers are uniformly dispersed with the nano-modified polyaniline material along with stirring, and the reinforcing filler, the modified fibers and the nano-modified polyaniline material play a mutual filling role; therefore, the mechanical property of the conductive composite polymer is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of conductive polymer materials, and in particular to an environmentally friendly nano-modified polyaniline composite material for electric power grounding bodies and a preparation process thereof. Background Art

[0002] The grounding body, also known as the grounding electrode, is a metal conductor or a group of conductors that are in direct contact with the soil. It is divided into artificial grounding bodies and natural grounding bodies. As a conductor that is in close contact with the earth's soil and provides an electrical connection with the earth, the grounding body safely disperses the lightning energy and discharges it into the earth.

[0003] Conductive polymers are a new type of functional polymer material that has the excellent mechanical properties and chemical stability of polymer materials and the good electrical conductivity of metal materials. The room temperature electrical conductivity can vary within the range of insulator semiconductor metal states. They have great application potential in the fields of power infrastructure, electromagnetic shielding, electronic devices such as transistors, and new energy. The research on conductive polymers has a history of more than 30 years. Great progress has been made in the mechanism, design and synthesis of materials, structure and performance, processability and stability, as well as the exploration of technical applications. Intrinsic conductive polymers such as polyacetylene, polypyrrole, polyaniline and polythiophene have been developed and are moving towards practical application. However, conductive polymers have problems such as high price, poor processability and poor stability, which have limited their practical applications.

[0004] Polyaniline has good electrical conductivity, stable structure and simple preparation. It can be used as a conductive filler and compounded with non-conductive polymers to prepare conductive composite polymers. Scholars have conducted a lot of research on adjusting the conductive and mechanical properties of composite materials by adding conductive fillers.

[0005] However, polyaniline is extremely difficult to dissolve, easily agglomerates, and is difficult to disperse in the matrix material, which is not conducive to the optimization of the conductive and mechanical properties of conductive composite polymers and has formed a major obstacle to its development. Summary of the invention

[0006] In order to improve the mechanical properties of conductive composite polymers, the present application provides an environmentally friendly nano-modified polyaniline composite material for electric power grounding bodies and a preparation process thereof.

[0007] In the first aspect, the present application provides an environmentally friendly nano-modified polyaniline composite material for electric power grounding body, which adopts the following technical solution:

[0008] An environmentally friendly nano-modified polyaniline composite material for electric grounding body comprises nano-modified polyaniline material, low-density polyethylene, styrene-butadiene thermoplastic elastomer and additives, wherein the weight ratio of the nano-modified polyaniline material, low-density polyethylene, styrene-butadiene thermoplastic elastomer and additives is (4-5):(10-11):(3-4):(1-2).

[0009] By adopting the above technical scheme, the polyaniline material is nano-modified and then mixed with low-density polyethylene, styrene-butadiene thermoplastic elastomer and additives to obtain a composite material. In this process, the dispersion uniformity of the polyaniline material in the composite material is improved, thereby effectively improving the mechanical properties of the composite material, so that the conductive composite polymer finally obtained can be suitable for a variety of environments.

[0010] Preferably, the additives include a coupling agent, an anti-aging agent and a flame retardant, and the weight ratio of the coupling agent, the anti-aging agent and the flame retardant is 2:2:3.

[0011] By adopting the above technical solution and using coupling agent, anti-aging agent and flame retardant as additives, the physical properties of the conductive composite polymer finally obtained can be further improved, thereby improving the applicability of the conductive composite polymer in various environments.

[0012] Preferably, the nano-modified polyaniline material is prepared by the following steps:

[0013] S1, ultrasonically dispersing 1 wt% of halloysite powder in water, and then adding a dopant to form a first step solution with a concentration of 0.1 mol / L-0.5 mol / L;

[0014] S2, according to the weight ratio of aniline monomer to halloysite powder, dissolving 0.5wt%-5wt% of aniline monomer in the first step solution to form a second step solution, and controlling the temperature of the obtained second step solution to be 0-4°C;

[0015] S3. According to the weight ratio of the oxidant to the aniline monomer, 1wt%-2wt% of the oxidant is added to the above second step solution, the temperature is controlled at 0-4°C, the reaction is stirred for 6-8h, centrifuged and washed three times with ethanol and deionized water respectively, and freeze-dried to obtain a nano-modified polyaniline material.

[0016] By adopting the above technical scheme, polyaniline is nano-modified by halloysite, and a core-shell structured nanocomposite material with halloysite as the core and polyaniline as the shell is prepared. The halloysite has excellent dispersibility and loading capacity, and its large surface area can provide more electrochemical active sites, and the hollow tubular structure can promote ion diffusion. Polyaniline is functionalized on the surface of halloysite, which can prevent polyaniline from aggregating, thereby improving the dispersibility and conductive properties of polyaniline. The halloysite itself has good mechanical strength and can play a nano-crosslinking role, and optimizes the mechanical properties of the composite material through physical interaction forces such as hydrogen bonds with the polymer matrix.

[0017] Preferably, the doping agent is hydrochloric acid or perchloric acid.

[0018] Preferably, the oxidant is ammonium persulfate.

[0019] Preferably, it further comprises reinforcing filler and modified fiber, and the weight ratio of the nano-modified polyaniline material, the reinforcing filler and the modified fiber is 11:2:2.

[0020] By adopting the above technical solution, during the preparation process of the conductive composite polymer, the reinforcing filler and the modified fiber are evenly dispersed with the nano-modified polyaniline material during stirring, and the three play a role of filling each other, thereby improving the mechanical properties of the conductive composite polymer.

[0021] Preferably, the reinforcing filler is silica-modified zirconium hydrogen phosphate.

[0022] By adopting the above technical solution, on the one hand, the elongation at break and the breaking strength of the conductive composite polymer are improved, so that the conductive composite polymer is not easily damaged, and on the other hand, the conductive performance of the conductive composite polymer is enhanced.

[0023] Preferably, the modified fiber is silica-modified lignocellulose.

[0024] By adopting the above technical solution, during the mixing process, the silicon dioxide modifies the wood cellulose so that the toughness of the conductive composite polymer is enhanced and its conductive performance is improved.

[0025] In the second aspect, the present application provides a preparation process of an environmentally friendly nano-modified polyaniline composite material for an electric power grounding body, which adopts the following technical solution:

[0026] A preparation process of an environmentally friendly nano-modified polyaniline composite material for an electric power grounding body comprises the following steps:

[0027] S1. According to the weight ratio, the nano-modified polyaniline material, low-density polyethylene, styrene-butadiene thermoplastic elastomer and additives are mixed evenly in a high-speed mixer, and then added into a torque rheometer for kneading for 3-5 minutes. At the same time, the temperature is controlled at 145°C and the speed is set at 50-70rpm;

[0028] S2. The material obtained from the first step of kneading is placed in a rectangular mold, and then placed in a flat vulcanizer for compression molding. The temperature is controlled at 145° C., the molding time is set to 3 min, and the material is cooled to obtain a nano-modified polyaniline composite material.

[0029] Preferably, the method comprises the following steps:

[0030] S1. According to the weight ratio, nano-modified polyaniline material, low-density polyethylene, and styrene are mixed.

[0031] -Butadiene thermoplastic elastomer, additive reinforcing filler and modified fiber are mixed evenly in a high-speed mixer, and then added into a torque rheometer for kneading for 3-5 minutes. At the same time, the temperature is controlled at 145°C and the speed is set at 50-70rpm;

[0032] S2. The material obtained from the first step of kneading is placed in a rectangular mold, and then placed in a flat vulcanizer for compression molding. The temperature is controlled at 145° C., the molding time is set to 3 min, and the material is cooled to obtain a nano-modified polyaniline composite material.

[0033] In summary, the present application includes at least one of the following beneficial technical effects:

[0034] 1. Halloysite was used to nano-modify polyaniline to prepare a core-shell structure nanocomposite with halloysite as the core and polyaniline as the shell. Halloysite has excellent dispersibility and loading capacity. Its large surface area can provide more electrochemical active sites, and its hollow tubular structure can promote ion diffusion. Polyaniline is functionalized on the surface of halloysite, which can prevent polyaniline from aggregating, thereby improving the dispersibility and conductivity of polyaniline. Halloysite itself has good mechanical strength and can play a nano-crosslinking role. It interacts with the polymer matrix through physical interactions such as hydrogen bonds to optimize the mechanical properties of the composite material.

[0035] 2. After the polyaniline material is nano-modified, it is mixed with low-density polyethylene, styrene-butadiene thermoplastic elastomer and additives to prepare a composite material. In this process, the dispersion uniformity of the polyaniline material in the composite material is improved, thereby effectively improving the mechanical properties of the composite material, so that the conductive composite polymer finally prepared can be applied to a variety of environments;

[0036] 3. During the preparation of the conductive composite polymer, the reinforcing filler and the modified fiber are evenly dispersed with the nano-modified polyaniline material during stirring, and the three play a role of filling each other, thereby improving the mechanical properties of the conductive composite polymer. DETAILED DESCRIPTION

[0037] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0038] In the present application, the coupling agent is KH560, the anti-aging agent is BASF 1010, the flame retardant is antimony trioxide flame retardant, the halloysite particle size is 50nm, the lignin fiber is 3mm long and 15μm in diameter, the silica powder particle size is 100nm, and other raw materials are purchased from the market.

[0039] Preparation example of nano-modified polyaniline material

[0040] Preparation Example 1

[0041] S1. Ultrasonic dispersion of halloysite powder in water for 30 minutes to prepare a 1 wt % halloysite aqueous dispersion, and then adding dopant hydrochloric acid to the dispersion to form a first step solution with a hydrochloric acid concentration of 0.1 mol / L.

[0042] S2. Count by mass, take 100 parts of the first step solution, add 3 parts of aniline monomer, and stir for 30 minutes to form a second step solution.

[0043] S3. Add 1.3 parts of oxidant ammonium persulfate to the obtained second step solution, control the temperature at 0-4°C, stir for 6 hours to obtain a light green suspension, use a centrifuge to centrifuge at 8000 rpm to obtain a product, and wash it three times with ethanol and deionized water respectively, and freeze-dry it for 12 hours to obtain a nano-modified polyaniline material.

[0044] The conductivity of the nano-modified polyaniline material was measured to be 5.2S / m.

[0045] Preparation Example 2

[0046] S1. Ultrasonic dispersion of halloysite powder in water for 30 minutes to prepare a 1 wt % halloysite aqueous dispersion, and then adding dopant hydrochloric acid to the dispersion to form a first step solution with a hydrochloric acid concentration of 0.1 mol / L.

[0047] S2. Count by mass, take 100 parts of the first step solution, add 5 parts of aniline monomer, and stir for 30 minutes to form a second step solution.

[0048] S3. Add 1.3 parts of oxidant ammonium persulfate to the obtained second step solution, control the temperature at 0-4°C, stir for 6 hours to obtain a light green suspension, use a centrifuge to centrifuge at 8000 rpm to obtain a product, and wash it three times with ethanol and deionized water respectively, and freeze-dry it for 12 hours to obtain a nano-modified polyaniline material.

[0049] The conductivity of the nano-modified polyaniline material was measured to be 5.7S / m.

[0050] Preparation Example 3

[0051] S1. Ultrasonic dispersion of halloysite powder in water for 30 minutes to prepare a 1 wt % halloysite aqueous dispersion, and then adding perchloric acid as a dopant to the dispersion to form a first step solution with a perchloric acid concentration of 0.1 mol / L.

[0052] S2. Count by mass, take 100 parts of the first step solution, add 5 parts of aniline monomer, and stir for 30 minutes to form a second step solution.

[0053] S3. Add 1.3 parts of oxidant ammonium persulfate to the obtained second step solution, control the temperature at 0-4°C, stir for 6 hours to obtain a light green suspension, use a centrifuge to centrifuge at 8000 rpm to obtain a product, and wash it three times with ethanol and deionized water respectively, and freeze-dry it for 12 hours to obtain a nano-modified polyaniline material.

[0054] The conductivity of the nano-modified polyaniline material was measured to be 5.1S / m.

[0055] By comparing the preparation examples 1-3, it can be seen that the ratio between halloysite and aniline monomer has a significant effect on the conductivity of the final nano-modified polyaniline material, and the use of hydrochloric acid as a dopant is significantly better than perchloric acid.

[0056] Preparation Example of Modified Zirconium Hydrogen Phosphate

[0057] Preparation Example 4

[0058] S1. Mix 1g of zirconium hydrogen phosphate with 50mL of n-butylamine solution, the concentration of which is 0.2mol / L, and then add 1g of silicon dioxide powder and stir for 12h. Use 0.2mol / L hydrochloric acid solution to adjust the pH to 2, and control the speed to 500rpm.

[0059] S2. The solid was filtered and washed with petroleum ether for several times, and then vacuum dried to constant weight.

[0060] By intercalating zirconium hydrogen phosphate with n-butylamine and loading silicon dioxide on zirconium hydrogen phosphate, the dispersion properties of zirconium hydrogen phosphate are utilized to make the nano-modified polyaniline material more evenly dispersed. At the same time, silicon dioxide is used to enhance the bonding strength between zirconium hydrogen phosphate and low-density polyethylene, and at the same time improve the conductive properties of the final polymer.

[0061] Modified lignin fiber preparation example

[0062] Preparation Example 5

[0063] S1. Mix lignin fiber with 1% by mass NaOH solution, the NaOH solution covers the lignin fiber, the reaction temperature is 30°C, the reaction time is 2h, and after the reaction is completed, wash with deionized water until the pH of the filtrate is neutral.

[0064] S2. Take 5 g of the lignin fiber treated in S1, place it in 50 mL of ethanol, add 3 g of silica powder, ultrasonicate for 10 min, filter and vacuum dry at 80 °C for 6 h to complete the modification.

[0065] By using silica to modify lignin fibers, the interfacial compatibility of lignin fibers with nano-modified polyaniline materials and modified zirconium hydrogen phosphate is improved when the bonding strength with low-density polyethylene is increased. As a result, the nano-modified polyaniline materials and zirconium hydrogen phosphate are evenly dispersed in the low-density polyethylene, thereby enhancing the toughness of the low-density polyethylene.

[0066] Example 1

[0067] A nano-modified polyaniline composite conductive polymer material is prepared by the following steps:

[0068] Parts are counted by weight.

[0069] S1. Mix 22 parts of the nano-modified polyaniline material obtained in Preparation Example 1, 53 parts of low-density polyethylene, 18 parts of styrene-butadiene thermoplastic elastomer, 2 parts of coupling agent, 2 parts of anti-aging agent, and 3 parts of flame retardant in a high-speed mixer, and then add them to a torque rheometer, control the temperature at 145°C, set the speed at 50-70rpm, and mix for 5 minutes.

[0070] S2, placing the kneaded material in a rectangular mold, and then placing it in a flat vulcanizer for compression molding, controlling the temperature at 145°C, setting the molding time to 3 minutes, and cooling to obtain a nano-modified polyaniline composite conductive polymer material.

[0071] Example 2

[0072] A nano-modified polyaniline composite conductive polymer material is prepared by the following steps:

[0073] Parts are counted by weight.

[0074] S1. Mix 22 parts of the nano-modified polyaniline material obtained in Preparation Example 2, 53 parts of low-density polyethylene, 18 parts of styrene-butadiene thermoplastic elastomer, 2 parts of coupling agent, 2 parts of anti-aging agent, and 3 parts of flame retardant in a high-speed mixer, and then add them to a torque rheometer, control the temperature at 145°C, set the speed at 50-70rpm, and mix for 5 minutes.

[0075] S2, placing the kneaded material in a rectangular mold, and then placing it in a flat vulcanizer for compression molding, controlling the temperature at 145°C, setting the molding time to 3 minutes, and cooling to obtain a nano-modified polyaniline composite conductive polymer material.

[0076] Example 3

[0077] A nano-modified polyaniline composite conductive polymer material is prepared by the following steps:

[0078] Parts are counted by weight.

[0079] S1. Mix 22 parts of the nano-modified polyaniline material obtained in Preparation Example 3, 53 parts of low-density polyethylene, 18 parts of styrene-butadiene thermoplastic elastomer, 2 parts of coupling agent, 2 parts of anti-aging agent, and 3 parts of flame retardant in a high-speed mixer, and then add them to a torque rheometer, control the temperature at 145°C, set the speed at 50-70rpm, and mix for 5 minutes.

[0080] S2, placing the kneaded material in a rectangular mold, and then placing it in a flat vulcanizer for compression molding, controlling the temperature at 145°C, setting the molding time to 3 minutes, and cooling to obtain a nano-modified polyaniline composite conductive polymer material.

[0081] Example 4

[0082] A nano-modified polyaniline composite conductive polymer material is prepared by the following steps:

[0083] Parts are counted by weight.

[0084] S1. Mix 22 parts of the nano-modified polyaniline material prepared in Preparation Example 2, 53 parts of low-density polyethylene, 18 parts of styrene-butadiene thermoplastic elastomer, 2 parts of coupling agent, 2 parts of anti-aging agent, 3 parts of flame retardant and 4 parts of modified zirconium hydrogen phosphate prepared in Preparation Example 4 in a high-speed mixer, and then add them to the torque rheometer, control the temperature at 145°C, set the speed at 50-70rpm, and mix for 5 minutes.

[0085] S2, placing the kneaded material in a rectangular mold, and then placing it in a flat vulcanizer for compression molding, controlling the temperature at 145°C, setting the molding time to 3 minutes, and cooling to obtain a nano-modified polyaniline composite conductive polymer material.

[0086] Example 5

[0087] A nano-modified polyaniline composite conductive polymer material is prepared by the following steps:

[0088] Parts are counted by weight.

[0089] S1. Mix 22 parts of the nano-modified polyaniline material obtained in Preparation Example 2, 53 parts of low-density polyethylene, 18 parts of styrene-butadiene thermoplastic elastomer, 2 parts of coupling agent, 2 parts of anti-aging agent, 3 parts of flame retardant and 4 parts of modified lignin fiber obtained in Preparation Example 5 in a high-speed mixer, and then add them to the torque rheometer, control the temperature at 145°C, set the speed at 50-70rpm, and mix for 5 minutes.

[0090] S2, placing the kneaded material in a rectangular mold, and then placing it in a flat vulcanizer for compression molding, controlling the temperature at 145°C, setting the molding time to 3 minutes, and cooling to obtain a nano-modified polyaniline composite conductive polymer material.

[0091] Example 6

[0092] A nano-modified polyaniline composite conductive polymer material is prepared by the following steps:

[0093] Parts are counted by weight.

[0094] S1. Mix 22 parts of the nano-modified polyaniline material prepared in Preparation Example 2, 53 parts of low-density polyethylene, 18 parts of styrene-butadiene thermoplastic elastomer, 2 parts of coupling agent, 2 parts of anti-aging agent, 3 parts of flame retardant, 4 parts of modified zirconium hydrogen phosphate prepared in Preparation Example 4 and 4 parts of modified lignin fiber prepared in Preparation Example 5 in a high-speed mixer, and then add them to the torque rheometer, control the temperature at 145°C, set the speed at 50-70rpm, and mix for 5 minutes.

[0095] S2, placing the kneaded material in a rectangular mold, and then placing it in a flat vulcanizer for compression molding, controlling the temperature at 145°C, setting the molding time to 3 minutes, and cooling to obtain a nano-modified polyaniline composite conductive polymer material.

[0096] Comparative Example 1

[0097] A nano-modified polyaniline composite conductive polymer material is prepared by the following steps:

[0098] Parts are counted by weight.

[0099] S1. Mix 10 parts of the nano-modified polyaniline material obtained in Preparation Example 1, 70 parts of low-density polyethylene, 12 parts of styrene-butadiene thermoplastic elastomer, 2 parts of coupling agent, 3 parts of anti-aging agent and 3 parts of flame retardant in a high-speed mixer, and then add them into a torque rheometer, control the temperature at 145°C, set the speed at 50-70rpm, and mix for 5 minutes.

[0100] S2, placing the kneaded material in a rectangular mold, and then placing it in a flat vulcanizer for compression molding, controlling the temperature at 145°C, setting the molding time to 3 minutes, and cooling to obtain a nano-modified polyaniline composite conductive polymer material.

[0101] Comparative Example 2

[0102] A nano-modified polyaniline composite conductive polymer material is prepared by the following steps:

[0103] Parts are counted by weight.

[0104] S1. Mix 30 parts of the nano-modified polyaniline material obtained in Preparation Example 3, 50 parts of low-density polyethylene, 13 parts of styrene-butadiene thermoplastic elastomer, 2 parts of coupling agent, 2 parts of anti-aging agent, and 3 parts of flame retardant in a high-speed mixer, and then add them to a torque rheometer, control the temperature at 145°C, set the speed at 50-70rpm, and mix for 5 minutes.

[0105] S2. Place the kneaded material in a rectangular mold, and then put it into a flat vulcanizer for compression molding, control the temperature at 145°C, set the molding time to 3 minutes, and cool it to obtain a nano-modified polyaniline composite conductive polymer.

[0106] Comparative Example 3

[0107] A nano-modified polyaniline composite conductive polymer material is prepared by the following steps:

[0108] Parts are counted by weight.

[0109] S1. Mix 22 parts of commercially available conductive polyaniline, 53 parts of low-density polyethylene, 18 parts of styrene-butadiene thermoplastic elastomer, 2 parts of coupling agent, 2 parts of anti-aging agent and 3 parts of flame retardant in a high-speed mixer, then add them into a torque rheometer, control the temperature at 145°C, set the speed at 50-70rpm, and mix for 5 minutes.

[0110] S2. Place the kneaded material in a rectangular mold, and then put it into a flat vulcanizer for compression molding, control the temperature at 145°C, set the molding time to 3 minutes, and cool it to obtain a nano-modified polyaniline composite conductive polymer.

[0111] Table 1 Performance data test table of embodiments and comparative examples

[0112] Resistivity (Ω·cm) Elongation at break (%) Tensile strength(MPa) Example 1 <![CDATA[9.62×10 3 ]]> / / Example 2 <![CDATA[3.78×10 3 ]]> 262 41.9 Example 3 <![CDATA[3.61×10 3 ]]> / / Example 4 <![CDATA[3.24×10 3 ]]> 271 45.4 Example 5 <![CDATA[3.86×10 3 ]]> 319 42.6 Example 6 <![CDATA[3.17×10 3 ]]> 336 47.1 Comparative Example 1 <![CDATA[3.16×10 5 ]]> / / Comparative Example 2 <![CDATA[5.37×10 4 ]]> / / Comparative Example 3 <![CDATA[6.62×10 5 ]]> 182 34.2

[0113] By comparing Example 2 with Comparative Example 3, polyaniline was nano-modified using halloysite to prepare a core-shell structured nanocomposite material with halloysite as a core and polyaniline as a shell. Halloysite has excellent dispersibility and loading capacity, and its large surface area can provide more electrochemical active sites, and its hollow tubular structure can promote ion diffusion. Polyaniline is functionalized on the surface of halloysite, which can prevent polyaniline from aggregating, thereby improving the dispersibility and conductivity of polyaniline. Halloysite itself has good mechanical strength and can play a nano-crosslinking role, and optimizes the mechanical properties of the composite material through physical interaction forces such as hydrogen bonds with the polymer matrix.

[0114] By comparing Example 2, Comparative Example 1 and Comparative Example 2, it is found that the conductive properties and mechanical properties of the final conductive composite polymer can be significantly affected by adjusting the addition ratio of the nano-modified polyaniline material.

[0115] By comparing Example 2 with Examples 4-6, n-butylamine is intercalated into zirconium hydrogen phosphate, and silicon dioxide is loaded on zirconium hydrogen phosphate. The dispersion property of zirconium hydrogen phosphate is utilized to make the nano-modified polyaniline material more evenly dispersed. At the same time, silicon dioxide is used to enhance the bonding strength between zirconium hydrogen phosphate and low-density polyethylene, and at the same time, the conductive properties of the final polymer are improved.

[0116] By using silica to modify lignin fibers, the interfacial compatibility of lignin fibers with nano-modified polyaniline materials and modified zirconium hydrogen phosphate is improved when the bonding strength with low-density polyethylene is increased. As a result, the nano-modified polyaniline materials and zirconium hydrogen phosphate are evenly dispersed in the low-density polyethylene, thereby enhancing the toughness of the low-density polyethylene.

[0117] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. An environmentally friendly nano-modified polyaniline composite material for electric power grounding body, characterized in that: The invention comprises nano-modified polyaniline material, low-density polyethylene, styrene-butadiene thermoplastic elastomer and additives, wherein the weight ratio of the nano-modified polyaniline material, low-density polyethylene, styrene-butadiene thermoplastic elastomer and additives is (4-5):(10-11):(3-4):(1-2).

2. The environmentally friendly nano-modified polyaniline composite material for electric power grounding body according to claim 1, characterized in that: The additives include a coupling agent, an anti-aging agent and a flame retardant, and the weight ratio of the coupling agent, the anti-aging agent and the flame retardant is 2:2:

3.

3. The environmentally friendly nano-modified polyaniline composite material for electric power grounding body according to claim 1, characterized in that: The nano-modified polyaniline material is prepared by the following steps: S1, ultrasonically dispersing 1 wt% of halloysite powder in water, and then adding a dopant to form a first step solution with a concentration of 0.1 mol / L-0.5 mol / L; S2, according to the weight ratio of aniline monomer to halloysite powder, dissolving 0.5wt%-5wt% of aniline monomer in the first step solution to form a second step solution, and controlling the temperature of the obtained second step solution to be 0-4°C; S3. According to the weight ratio of the oxidant to the aniline monomer, 1wt%-2wt% of the oxidant is added to the above second step solution, the temperature is controlled at 0-4°C, the reaction is stirred for 6-8h, centrifuged and washed three times with ethanol and deionized water respectively, and freeze-dried to obtain a nano-modified polyaniline material.

4. The environmentally friendly nano-modified polyaniline composite material for electric power grounding body according to claim 3, characterized in that: The doping agent is hydrochloric acid.

5. The environmentally friendly nano-modified polyaniline composite material for electric power grounding body according to claim 3, characterized in that: The oxidant is ammonium persulfate.

6. The environmentally friendly nano-modified polyaniline composite material for electric power grounding body according to claim 1, characterized in that: It also includes reinforcing fillers and modified fibers, and the weight ratio of the nano-modified polyaniline material, the reinforcing fillers and the modified fibers is 11:2:

2.

7. The environmentally friendly nano-modified polyaniline composite material for electric power grounding body according to claim 6, characterized in that: The reinforcing filler is silicon dioxide modified zirconium hydrogen phosphate.

8. The environmentally friendly nano-modified polyaniline composite material for electric power grounding body according to claim 6, characterized in that: The modified fiber is silicon dioxide modified wood cellulose.

9. The method for preparing an environmentally friendly nano-modified polyaniline composite material for electric power grounding body according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. According to the weight ratio, the nano-modified polyaniline material, low-density polyethylene, styrene-butadiene thermoplastic elastomer and additives are mixed evenly in a high-speed mixer, and then added into a torque rheometer for kneading for 3-5 minutes. At the same time, the temperature is controlled at 145°C and the speed is set at 50-70rpm; S2. The material obtained from the first step of kneading is placed in a rectangular mold, and then placed in a flat vulcanizer for compression molding. The temperature is controlled at 145° C., the molding time is set to 3 min, and the material is cooled to obtain a nano-modified polyaniline composite material.

10. The method for preparing an environmentally friendly nano-modified polyaniline composite material for electric power grounding body according to any one of claims 6 to 8, characterized in that: The following steps are involved: S1. According to the weight ratio, the nano-modified polyaniline material, low-density polyethylene, styrene-butadiene thermoplastic elastomer, additive reinforcing filler and modified fiber are mixed evenly in a high-speed mixer, and then added into a torque rheometer for kneading for 3-5 minutes. At the same time, the temperature is controlled at 145°C and the speed is set at 50-70rpm; S2. The material obtained from the first step of kneading is placed in a rectangular mold, and then placed in a flat vulcanizer for compression molding. The temperature is controlled at 145° C., the molding time is set to 3 min, and the material is cooled to obtain a nano-modified polyaniline composite material.

Citation Information

Patent Citations

  • Method for preparing PTC (positive temperature coefficient) material by compounding polyaniline / carbon black / polyolefin

    CN103483666A

  • Method of lignin and silicon dioxide composite modified natural rubber master batch

    CN106750584A

  • Preparation method for corncob-shaped polyaniline-supported halloysite nanotube modified polypropylene

    CN108264686A

  • Halloysite nanotube cooperatively flame-retardant polyethylene material and preparation method thereof

    CN109021363A

  • Energy-saving environment-friendly water storage barrel with protective shell and manufacturing method thereof

    CN112480507A